Radiative Impact of Fireworks at a Tropical Indian Location: A Case Study - B. P. Singh; A. K. Srivastava; S. Tiwari; S. Singh; R. K. Singh; D. S. Bisht; D. M. Lal; A. K. Singh; R. K. Mall; Manoj K. Srivastava (Advances in Meteorology)
During Diwali festival, extensive burning of crackers and fireworks is made. Weeklong intensive observational campaign for aerosol study was carried out at a representative urban location in the eastern Indo-Gangetic Plain (IGP), Varanasi (25.3°N, 83.0°E), from October 29 to November 04, 2005 (Diwali on November 01, 2005), to investigate behavioral change of aerosol properties and radiative forcing between firework affected and nonaffected periods. Results show a substantial increase (~27%) in aerosol optical depth, aerosol absorption coefficients, and aerosol scattering coefficients during affected period as compared to non-affected periods. Magnitudes of radiative forcing at top of atmosphere during affected and non-affected periods are found to be +10 ± 1 and +12 ± 1 Wm−2, respectively, which are −31 ± 7 and −17 ± 5 Wm−2, respectively, at surface. It suggests an additional cooling of ~20% at top of atmosphere, ~45% cooling at surface, and additional atmospheric heating of 0.23 Kday−1 during fireworks affected period, which is ~30% higher than the non-affected period average.